PLAYING ONLINE GAMES AND ITS IMPACT ON ELEMENTARY SCHOOL STUDENTS' LEARNING RESPONSIBILITIES - Marwan Supriyanto; Aliet Noorhayati Sutisno; Fanny Septiany Rahayu (Universitas Majalengka, 2025)
This study aims to determine the effect of playing online games on the learning responsibility behavior of fourth-grade students at SDN 1 Watubelah. Online games have become part of children's daily lives, including elementary school students, so it is important to see how this activity impacts their academic attitudes and behavior. This study used a quantitative approach with a survey method. The sample in the study consisted of 33 students who were selected purposively. The instrument used was a questionnaire with a Likert scale to measure the intensity of playing games and learning responsibility. The results showed that most students had a high intensity of playing games, both in terms of duration, frequency, and less than ideal time. In addition, more than half of the students showed symptoms of decreased learning responsibility, such as frequently procrastinating assignments, lack of discipline, and loss of focus while studying.